Analyses of marginal seals in aged amalgam restorations using extraction replicas - Grossman, E. S.; Witcomb, M. J.; Jodaikin, A (My University, 1984)
Since dental amalgam does not bond chemically to tooth structure, a microcrevice is present at the amalgam/tooth interface of a freshly placed restoration. This gap is of sufficient width to allow fluids and microorganisms to pass along the cavity walls and thereby facilitating the recurrence of dental caries, which accounts for the majority of amalgam restoration replacements.
MRC/University of the Witwatersrand, Dental Research Institute, Johannesburg Electron Microscope Unit, University of the Witwatersrand, Johannesburg
Keywords: Dental Amalgam; Occlusal Adjustment; Tooth Wear